PEMBELAJARAN METODE CIRC DENGAN MEDIA MICROSOFT POWERPOINT TERHADAP PRESTASI BELAJAR SISWA KELAS X SMA NEGERI 2 TAMBUSAI TAHUN PEMBELAJARAN 2014/2015 - AZIZAH, ATIK (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
This study was aimed to of determine there is or not effect of CIRC (Cooperative Integrated Reading And Composition) learning method with media Microsoft powerpoint toward student achievement of class X SMA Negeri 2 Tambusai learning year 2014/2015. This was a quasi-experiment study with Non Randomized Control Group Pretest Posttest Design. Samples were collected with non random sampling method. The samples are the student at grade XA as experiment and grade XB as control. Data collecting technique in this study was a test instrument with multiple choice questions form. Hypothesis of results showed that the tcount > ttable (4,02 > 2,01). In conclution that the CIRC (Cooperative Integrated And Reading Composition) learning method with media Microsoft Powerpoint give effect toward student achievement of class X SMA Negeri 2 Tambusai learning year 2014/2015.Â